Underlying factors impacting vaccine hesitancy in high income countries: a review of qualitative studies - Eve Dubé; Dominique Gagnon; Noni MacDonald; Aurélie Bocquier; Patrick Peretti-Watel; Pierre Verger (Taylor & Francis Group, 2018)
Introduction. While the scientific consensus on the benefits of vaccination is unambiguous, there is a growing proportion of the population that is skeptical about vaccination. The idea that vaccination programs are losing their momentum concerns public health agencies throughout the world. Many studies assessing determinants of vaccine acceptance have been published in the last decade. Areas covered. In this article, we review the existing qualitative literature on parents' attitudes toward childhood vaccination. Studies were included if they: (1) focused on the views, decision-making, or experiences of caregivers (hereafter, referred to as 'parents') regarding vaccinations for young children; (2) used qualitative methods for both data and data analysis; (3) were conducted in countries that ranked 'very high' on the 2016 United Nations Human Development Index; and (4) had been peer-reviewed. Twenty-two (22) studies met our inclusion criteria and were reviewed, using the socio-ecological model as a conceptual framework. Expert commentary. Parental vaccination decisions are complex and multi-dimensional. Experiences, emotions, routine ways of thinking, information sources, peers/family, risk perceptions, and trust, among other factors, inform parents' attitudes and decision-making processes. Further research is needed in order to design evidence-informed responses to vaccine hesitancy appropriate to the setting, context, and hesitant subgroups.